Kajian Ayat-Ayat Manajemen: Isyarat Al-Qur’an Tentang Lingkungan Pendidikan - Husaini, Husaini (Institut Agama Islam Negeri Lhokseumawe, 2021)
The educational environment or also known as Tri Centa Pendidikan as an Education Center consisting of family, school, and community is a place where formal and non-formal educational interactions take place. The family as the first place has the responsibility to provide the initial foundation in education that colors the daily life of a child's personal life towards adulthood for the rest of his life. Schools as formal educational institutions are entrusted with the responsibility to continue children's education in developing talents and interests so that they become self-directed. Both families, schools and communities play a very important role and are responsible for supervising, directing, and providing the education they have received from adults or the surrounding environment. These three educational environments will greatly determine the development of children, whether good or bad, the role of parents, teachers and the surrounding community will affect the child's development. imitating and playing an active role in maturation of children's personal development through social interactions in daily life without us realizing that children will grow and develop both physically and spiritually and continue to experience continuous changes throughout life.